Chemical constituents from the roots and rhizomes of Silene tatarinowii Regel. (October 2019) - Liang, Xiaofei; Li, Yuze; Fan, Hao; Huang, Wenli; Zhang, Huawei; Cui, Yuwen; Song, Xiaomei
Abstract: Chemical investigation of the root and rhizome of Silene tatarinowii Regel led to the isolation of nine ecdysteroids (1–9 ) and one sterol (10 ). All the compounds were determined on the basis of MS and NMR and by comparison with those in the literature. All these compounds were isolated from S. tatarinowii for the first time. Furthermore, compounds7 –10 were isolated from Silene genus for the first time, of which compounds7 and8 were isolated from Caryophyllaceae family members for the first time. This is the first study to report the chemical constituents of S. tatarinowii and the chemotaxonomic relationships between Silene and other genera of Caryophyllaceae. Graphical abstract: Image 1 Highlights: ● Ten compounds were isolated for the first time from the roots and rhizomes of Silene tatarinowii. ● The compounds were assigned as ecdysteroids and sterol. ● First study to report these compounds in S. tatarinowii. ● Compounds7–10 were identified for the first time from the genus Silene, and compounds7, 8 were new for the family of Caryophyllaceae.